Ameliorative effect of palm oil tocotrienol rich fraction on brain oxidative stress in fenitrothion-administered rats - Siti Balkis Budin,; Izatus Shima Taib,; Putri Ayu Jayusman,; Hui, Hui Chiang; Anand Ramalingam,; Ahmad Rohi Ghazali,; Jamaludin Mohamed, (Universiti Kebangsaan Malaysia, 2014)
Fenitrothion (FNT) usage has received much attention for its potential to promote free radicals generation and interfere with antioxidant defense system. The aim of the present study was to investigate the effect of palm oil tocotrienol rich fraction (TRF) supplementation on oxidative stress and histological changes in rat brain induced by FNT. A total of 32 male Sprague Dawley rats divided into four groups: control group which received corn oil; TRF group was received palm oil TRF (200 mg/kg bw); FNT group administered with FNT (20 mg/kg bw) and TRF+FNT group pretreated with palm oil TRF (200 mg/kg bw) 30 min prior to administration of FNT (20 mg/kg bw). FNT and TRF were dissolved in corn oil and all supplementations were given by oral gavage once daily for 28 days. After four weeks of supplementation, TRF+FNT rats had significantly lower malondialdehyde (MDA) content and superoxide dismutase (SOD) activity but higher reduced glutathione (GSH) level and total protein level compared to FNT rats (p<0.05). However, protein carbonyl (PC) level was insignificantly lower for TRF+FNT group compared to FNT group. In conclusion, this study suggested that palm oil TRF was effective in preventing brain damage in rats.